An open label study on Depression Patient’s Disability Outcomes: Comparative Evaluation of Escitalopram and Amisulpride - Kaul, Vijay; Dutta, Shaktibala; Beg, Mirza Atif; Singh, Nand Kishore; Bawa, Shalu; Anjoom, Mohammed; Dutta, Srihari; Rai, Prithi (Journal of Nobel Medical College, 2016)
Background Depression is an important global public health problem due to its relatively high lifetime prevalence and significant disability caused by it. The present study was conducted to compare improvement in disability outcome by Amisulpride and Escitalopram among depression patients using WHO-Disability Assessment Schedule (WHO-DAS). Materials and Methods The study was conducted in depression patients for 1 year in the Department of Neuropsychiatry, Nepalgunj Medical College & Teaching Hospital. A total of 117 depression patients were divided into 2 groups. Group I (58 patients) received Amisulpride tablet at a dose of 50 mg/day and Group II (59 patients) were given Escitalopram at a dose of 10 mg/day. The patients were required to follow up at 4 weeks, 8 weeks and at 15 weeks. The efficacy of the drugs was calculated by Hamilton depression rating scale (HAM-D). The improvement in functional outcome was compared between the two groups by using WHO-Disability Assessment Schedule (WHO-DAS). Appropriate statistical tools using GraphPadInstat 3.0 were used for analysis. p value < 0.05 was considered significant. Results HAM-D score in group receiving Amisulpride at 0 and 15 weeks was 16.92±0.35 and 7.87±0.29 (p<0.0001). HAM-D score in group receiving Escitalopram at 0 and 15 weeks was 17.09±0.39 and 6.63±0.39 (p<0.0001). WHO-DAS score in group receiving Amisulpride at 0 and 15 weeks was 112.54±0.82 and 43.08±1.41 (p<0.0001) respectively. WHO-DAS in group receiving Escitalopram at 0 and 15 weeks was 113.73±1.92 and 40.69±1.49 (p<0.0001) respectively. Intergroup comparison at 15 weeks was insignificant (p>0.05). Gastrointestinal disturbances, sexual disturbances, amenorrhea, lactation, agitation and insomnia were the commonly encountered adverse drug reactions. Conclusion Both Amisulpride and Escitalopram showed improvement in WHO Disability Assessment Score (WHO-DAS) at the end of study period. But intergroup comparison showed no significant difference in the two groups. Journal of Nobel Medical College Vol.5(2) 2016; 37-42